Prevalence and reliability of treatment-based classification for subgrouping patients with low back pain. (1st January 2018) - de Oliveira, Isadora Orlando; de Vasconcelos, Rodrigo Antunes; Pilz, Bruna; Teixeira, Paulo Eduardo Portes; de Faria Ferreira, Eduarda; Mello, Wilson; Grossi, Débora Bevilaqua
Abstract: Objectives : To observe the distribution of patients who presented with low back pain (LBP) and to determine the between therapists' interrater reliability of assessments in a private outpatient setting using treatment-based classification (TBC) subgroups. Methods : An observational and methodological study was conducted. Four hundred and twenty-nine patients (231 male; 198 female) presenting LBP symptoms and referred to conservative treatment were assessed by 13 physical therapists who conducted a 60-min examination process utilizing TBC subgroups. Interrater reliability analyses from six raters were assessed using Fleiss' kappa and previously recorded data ( n = 30). Results : In this study, 65.74% of patients were classified in only one subgroup, the most prevalent being stabilization (21.91%), followed by extension (15.38%), traction (11.89%), flexion (10.96%), manipulation (5.13%), and lateral shift (0.47%). Approximately 20.98% of patients were classified in two subgroups, where the most frequent overlaps were flexion + stabilization (7.46%), extension + stabilization (6.06%), flexion + traction (4.20%), extension + manipulation (1.86%), and 13.29% of patients were not classified in any TBC subgroup. Analysis of interrater reliability showed a kappa value of 0.62 and an overall agreement of 66% between raters. Discussion : LBP is a heterogeneous clinical condition and several classification methods are proposed in the attempt to observe better outcomes for patients. Eighty-five percent of patients assessed were able to be classified when using the TBC assessment and reliability analysis showed a substantial agreement between raters. Level of Evidence : 2c.